DEVELOPING INTERACTIVE MULTIMEDIA FOR TEACHING READING SKILL NARRATIVE TEXT FOR NINTH GRADE STUDENTS OF JUNIOR HIGH SCHOOL - Daryusman, Karsa; Susilawati, Endang; Rahmani, Eka Fajar (Universitas Tanjungpura, 2023)
This research aims to develop interactive multimedia as a teaching and learning media to teach reading narrative text to the ninth-grade student